Pelaksanaan Pembelajaran Tatap Muka Terbatas Perspektif Sosiologi Pendidikan - Muhammad Yasin (Jurnal Riset Madrasah Ibtidaiyah, 2023)
Implementation of Limited Face-to-Face Learning (PTMT) refers to policies in several countries, including Indonesia, as a response to the COVID-19 pandemic. In the midst of a pandemic, education that was previously carried out entirely face-to-face in schools has been changed to distance learning or daring to reduce the spread of the virus. The purpose of this study is to describe face-to-face learning at Muhammadiyah 2 North Sangatta Elementary School and how teachers and principals implement limited face-to-face learning. This study uses a descriptive approach with qualitative research methods with the aim of observing more closely at natural objects. The descriptive method is a method that focuses on a group of people, conditions, an object and an event in the present. The results of the research are that the Muhammadiyah 2 Elementary School implements limited face-to-face learning carried out systematically, where the school principal and the Elementary School have implemented limited face-to-face learning, where the teaching and learning process in class, protective material is condensed and only with a chart scheme or by way of mapping so that it is easy absorbed by students, then for direct supervision of school principals and from primary and secondary education under the Muhammadiyah Islamic organization, and then structured and measurable evaluation.